Corpus linguistics for translation and contrastive studies a guide for research - Mikhailov, Mikhail; Cooper, Robert (Routledge Corpus Linguistics Guides, 2016)
Corpus Linguistics for Translation and Contrastive Studies provides a clear and practical introduction to using corpora in these fields. Giving special attention to parallel corpora, which are collections of texts in two or more languages, and demonstrating the potential benefits for multilingual corpus linguistics research to both translators and researchers. This book explores the different types of parallel corpora available, and shows how to use basic and advanced search procedures to analyse them ; explains how to compile a parallel corpus, and discusses their uses for translation purposes and to research linguistic phenomena across languages ; demonstrates the use of corpus extracts across a wide range of texts, including dictionaries, novels by authors including Jane Austen and Mikhail Bulgakov, and newspapers such as The Sunday Times ; is illustrated with case studies from a range of languages including Finnish, Russian, English and French. Written by two experienced researchers and practitioners, Corpus Linguistics for Translation and Contrastive Studies is essential reading for postgraduate students and researchers working within the area of translation and contrastive studies. -- Provided by publisher.